2011
DOI: 10.1203/pdr.0b013e3182072229
|View full text |Cite
|
Sign up to set email alerts
|

Th1 and Th2 Chemokines, Vaccine-Induced Immunity, and Allergic Disease in Infants After Maternal ω-3 Fatty Acid Supplementation During Pregnancy and Lactation

Abstract: ABSTRACT:We investigated whether the previously reported preventive effect of maternal -3 fatty acid supplementation on IgEassociated allergic disease in infancy may be mediated by facilitating a balanced circulating Th2/Th1 chemokine profile in the infant. Vaccine-induced immune responses at 2 y of age were also evaluated. Pregnant women, at risk of having an allergic infant, were randomized to daily supplementation with 1.6 g eicosapentaenoic acid and 1.1 g docosahexaenoic acid or placebo from the 25th gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 33 publications
3
28
0
2
Order By: Relevance
“…All of these studies reported some positive findings on selected immune markers and/or the incidence of (allergic) diseases in the children of supplemented mothers. Supplementation with LC-PUFA or consumption of 2 portions of oily fish/week during pregnancy resulted in improvements in neonatal [50,51,52,53] and maternal [53,54] immune responses, with attenuation of allergic inflammation, perhaps influenced by the infant allergic status.…”
Section: Resultsmentioning
confidence: 99%
“…All of these studies reported some positive findings on selected immune markers and/or the incidence of (allergic) diseases in the children of supplemented mothers. Supplementation with LC-PUFA or consumption of 2 portions of oily fish/week during pregnancy resulted in improvements in neonatal [50,51,52,53] and maternal [53,54] immune responses, with attenuation of allergic inflammation, perhaps influenced by the infant allergic status.…”
Section: Resultsmentioning
confidence: 99%
“…Our chemokine data revealed an association between increased CCL17 levels at birth and at 24 months of age and development of AD (described in paper II and III). The relationship between elevated CCL17 levels and AD development during infancy, regardless of sensitisation, has been confirmed in 2 other cohorts of children (paper SII, [208,221]). …”
Section: Th1-and Th2-like Immunity At Birth and During Childhood In Amentioning
confidence: 60%
“…One study, from which 2 articles were published, was performed in preterm infant. Two published studies from the same group were from Australia (Manley et al 2011;Atwell et al 2013), 1 in Denmark (Lauritzen et al 2005), and 3 studies from the same group were done in Sweden (Furuhjelm et al 2009(Furuhjelm et al , 2011a(Furuhjelm et al , 2011b. Four of the trials included markers of immune function or incidence of allergic and atopic diseases as the primary outcome, and the secondary outcome for the remaining 2 trials.…”
Section: Introductionmentioning
confidence: 99%
“…A dysregulation in the Th1/Th2 response has been proposed to be one of the mechanisms involved in development of allergic and atopic diseases (Prescott and Dunstan 2007). They reported that maternal fish oil supplementation differentially affected the Th1 response in infants according to their allergic status (i.e., different response in infant with and without a maternal history of allergy) (Furuhjelm et al 2011a). This suggests that the impact of maternal DHA supplementation on the development of the immune system and the establishment of oral tolerance may differ based on the family history of allergic and atopic diseases, which are important considerations in future research.…”
Section: Introductionmentioning
confidence: 99%